Influence of Bacillus subtilis strain Z-14 on microbial communities of wheat rhizospheric soil infested with Gaeumannomyces graminis var. tritici - Liu, Zhaosha; Xiao, Jiawen; Zhang, Xuechao; Dou, Shijuan; Gao, Tongguo; Wang, Dongmei; Zhang, Dongdong (Frontiers in Microbiology, 2022)
Wheat take-all disease caused by Gaeumannomyces graminis var. tritici (Ggt) spreads rapidly and is highly destructive, causing severe reductions in wheat yield. Bacillus subtilis strain Z-14 that significantly controlled wheat take-all disease effectively colonized the roots of wheat seedlings. Z-14 increased the metabolic activity and carbon source utilization of rhizospheric microorganisms, thus elevating average well-color development (AWCD) values and functional diversity indexes of soil microbial communities. Z-14 increased the abundance of Bacillus in the rhizosphere, which was positively correlated with AWCD and functional diversity indexes. The Z-14-treated samples acquired more linkages and relative connections between bacterial communities according to co-occurrence network analyses. After the application of Ggt, the number of linkages between fungal communities increased but later decreased, whereas Z-14 increased such interactions. Whole-genome sequencing uncovered 113 functional genes related to Z-14’s colonization ability and 10 secondary metabolite gene clusters in the strain, of which nine substances have antimicrobial activity. This study clarifies how bacterial agents like Z-14 act against phytopathogenic fungi and lays a foundation for the effective application of biocontrol agents.